Utilization of the Coastal Area as a Settlement Area by the Bajo Tribe in Torosiaje Sea Village - Kumala Ilyas (Golden Ratio of Law and Social Policy Review (GRLSPR), 2022)
This study aims to determine the role of the government in the utilization of the Coastal Area as a residential area by the Bajo tribal community in Torosiaje Sea Village. This research was conducted in Torosiaje Village, Popayato Subdistrict, Pohuwato Regency, District Land Service. Pohuwato, Department of Housing and Settlement Area of Pohuwato Regency, Department of Forestry Kab. Pohuwato, by determining the research sample includes: Head of Service, Village Head and the community of Torosiaje Sea Village, Pohuwato Regency. The data used are primary data, namely data obtained directly from the field using interview techniques, as well as secondary data in the form of observations and observations of data from related agencies. The data analysis used is qualitative analysis with inductive conclusion drawing. The results of this study found that the role of the government for the use of coastal areas as residential areas for the Bajo community, in this case the Pohuwato District Forestry Service, Pohuwato District Land Service, and the Torosiaje Sea Village government, was to assist and issue certificates of use rights, thereby strengthening the legal power of the community's place of residence. bajo